2017
DOI: 10.11118/actaun201765051767
|View full text |Cite
|
Sign up to set email alerts
|

The Comparison of Customer Relationship Management (Crm) in Czech Small and Medium Enterprises According to Selected Characteristics in the Years 2015, 2010 and 2005

Abstract: To compare the level of contact with customers, 4 ways of contacting them were selected. Adverse developments showed up for the customer records, higher was its randomness, which was not expected. More sophisticated ways of contacting customers confirmed a positive change, though not very significant. The most important result in 2005 and 2015 was the increase in the number of loyal customers, which contributes to the growth of profitability. In the end of the article, hypothesis about the relationship of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…Only a small number of SMEs considered CRM ineffective. Also, both surveys from the Czech Republic and our findings partially confirmed that the use of CRM grows in terms of the size of the business was almost the same [1,17,67,79]. Following the results mentioned in our paper, in the case of clusters 1 and 2 (mainly consisting of micro-and small enterprises with no significant difference in terms of the enterprise size), there are various approaches to creating and using customer database between studied groups.…”
Section: Verification Of Working Hypotheses and Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Only a small number of SMEs considered CRM ineffective. Also, both surveys from the Czech Republic and our findings partially confirmed that the use of CRM grows in terms of the size of the business was almost the same [1,17,67,79]. Following the results mentioned in our paper, in the case of clusters 1 and 2 (mainly consisting of micro-and small enterprises with no significant difference in terms of the enterprise size), there are various approaches to creating and using customer database between studied groups.…”
Section: Verification Of Working Hypotheses and Discussionsupporting
confidence: 85%
“…Conversely, 45% of SMEs use CRM, 3% of SMEs are in the implementation phase, 21% of SMEs consider the implementation, and 31% of SMEs do not consider implementing CRM (especially micro-enterprises). The research from the Moravian-Silesian region also presents interesting results [67]. Knowledge of the concept of CRM in SMEs was enhanced by 39% in the last 5 years.…”
Section: Verification Of Working Hypotheses and Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…4.3). CRM solutions compile data from a range of different communication channels, including a company's website, telephone, email, live chat, marketing materials, and more recently, social media (Starzyczna et al 2017;Yerpude and Kumar Singhal 2018). Through the CRM approach and the systems used to facilitate it, businesses learn more about their target audiences and how to best cater to their needs.…”
Section: • Customer Relationship Management (Crm)mentioning
confidence: 99%
“…The SME sector influences has a key role in a currently highly competitive environment that is characteristic of the globalization process. It is imperative to acquire customers and maintain them so that this relationship would bring good economic results to the company (Starzyczná, Pellešová, Stoklasa 2017). The position of SMEs on the market is not simple.…”
Section: Introductionmentioning
confidence: 99%